Research Progress and Analysis of Moxibustion in Prevention and Treatment of Acute Infectious Diseases - Haiyan Li; Chao Zhang (Wolters Kluwer Health/LWW, 2020)
To introduce and evaluate current research progress of moxibustion in the prevention and treatment of acute infectious diseases, related literature in CNKI, Wanfang Data, and SinoMed was retrieved and analyzed by the present study. Results showed abundant studies on the mechanism of action of moxibustion in the prevention and treatment of acute infectious diseases with remarkable clinical efficacy. The present study also summarizes the commonly-occurring problems and found out the deficiencies in existing studies in hope of providing more reference for further research.